Management sf spot blotch of wbed (Triticum aestivum) caused by Biopolaris sorokiniana* - SINGH, V; SINGH, R N (The Indian Journal of Agricultural Sciences, 2011)
Experiments were conducted during 2001-02 to 2003- 04 crop seasons on the management of spot blotch of wheat (Triticum aestivum L. emend. Fiori & Paol.) caused by Bipolaris sorokiniana (Sacc. in Sorok.) Shoem. Noranal sown varieties ’HD 2733’, ’PEW 343’, W NW012’, ’IID 2824’ proved moderately susceptible and yielded 4.37, 4.50,4.12 and 4.37 tonnes/ha respectively. Late sown varieties ’PBW 373’ and ’NW 1014’ proved moderately resistant and yielded 3.55 and 3.70 tonnes/ha respectively. Out of 444 germplasm lines, 147 proved moderately resistant. Most promising of these, with lowest AUDPCs of 36.25 to 40.0 were ’ N S 17’, ’HS 422’, ’VW 0102’,’VW 0105’, ’VW 0107’, ’VW O1OS1, and ’VW 0109’. Propiconazole 25 EC applied @ 0.75 litreha at booting and soft dough stages, with disease intensities of 42.77 and 48.33% and grain yield of 4.43 and 3.81 tonnes/ha in tbe first and second years respectively, proved most effective in managing spot blotch. With a benefit:cost ratio of 2.15, it proved most economical in the second year when disease intensity was higher (79.77%). Two sprays of 0.75 litre/ha favored all the yield contributory characters.